Análise de desempenho de uma rede de distribuição de energia elétrica em baixa tensão alternada e contínua - Marcos Fernando dos Santos (2014)
The electric power distribution began with a system of direct current (DC), built by Thomas Edison. Shortly thereafter, Nikola Tesla and George Westinghouse built a system of alternating current (AC), which was to become almost the standard in the world. Few electrical systems currently operate on DC voltage, although the consumer electronics using this type of power for its internal circuitry and having power supplies (interface with the system of alternating voltage) that, in most cases, could be used directly DC voltages. With the development of power electronics, the adequacy of voltage levels for transmission and final use of electricity is no longer a barrier for systems of DC voltage. Some renewable energy sources are inherently DC voltage, such as fuel cells and photovoltaic panels, and the use of DC voltage allows the use of energy storage devices in networks, which can increase their robustness against short duration voltage variations. It is possible also improve the efficiency of some residential motor electrical appliances using variable frequency drives. The main objective of this work is to propose and study a electric power distribution system in DC voltage that is compatible with AC voltage levels currently in use. Based on the Survey of Equipment Ownership and Use Behavior - Residential Class - Southeast Region of Brazil, held by Procel / Eletrobras in 2005, a model was developed for a network with 50 consumers with different profiles of ownership and consumption habits of electric energy. The focus of the analysis, conducted from simulations of the proposed system in PowerFactory (DIgSILENT GmbH) software is the performance of low-voltage distribution network and the voltage drops and losses in circuits, on AC and DC voltage.